Adventures with instruments: science and seafaring in the precarious career of Christopher Middleton. (19th December 2018) - Bennett, Jim
Abstract : Christopher Middleton (d. 1770) was a sea captain, first with the Hudson's Bay Company, then in the Royal Navy, who was awarded the Royal Society's Copley Medal in 1742. His early work on magnetic variation in northern latitudes was encouraged by Edmond Halley, as he published a series of tables of variation in the Philosophical Transactions . These tables illustrate Middleton's transition from the priorities characteristic of the seaman's interest in variation to the wider, natural philosophical agenda of the Society. They illustrate also his enthusiasm for novel instrumentation, in particular altitude instruments for use at sea, such as Hadley's quadrant. Middleton was persuaded by Arthur Dobbs to resign from the Hudson's Bay Company and accept a commission in the Royal Navy so as to command an expedition to search for a Northwest Passage to the East Indies from Hudson's Bay. It was his report on this voyage that won him the Copley Medal but which also led to a bitter and, for Middleton, ruinous public dispute with Dobbs. Middleton emerges as an outstanding seaman and a worthy, if relatively unknown, medallist.